The Urban Renewable Energy Transition: Impact Assessment and Transmission Mechanisms of Climate Policy Uncertainty - Gao, Da; Zhang, Tianyi; Liu, Xiaowei (Energies (Basel), 2025)
The transition to renewable energy is a critical pathway for achieving low-carbon development and addressing global climate change problems. Therefore, we expand the conventional province-level energy balance table to the urban level, providing a refined assessment tool for evaluating renewable energy transition (RET). This study investigates the impact of climate policy uncertainty (CPU) on urban RET and explores the underlying mechanisms. The findings reveal that CPU significantly inhibits urban RET, with this effect being particularly pronounced in non-capital and inland cities. The mechanisms through which CPU hinders urban RET include exacerbating capital and labor misallocation and suppressing industrial structure upgrading. Furthermore, the moderation model indicates that high-intensity government supervision and low public environmental awareness exacerbate the negative impact of CPU on urban RET. Our findings provide governments with adopting forward-looking climate policies to mitigate the adverse effects of urban renewable energy transition.